Pembelajaran daring kemampuan berpikir kritis materi jenis usaha dan kegiatan ekonomi di indonesia pada siswa kelas V SD Atta’zhimiyah kota Bandung dengan metode kontekstual menggunakan video pembelajaran - Jajah Ratna Katidjah; Sukma Murni; Febri Restu Widianto (COLLASE (Creative of Learning Students Elementary Education), 2024)
This study aims to examine the learning of critical thinking skills on the type of business and economic activity in Indonesia in class V students with contextual methods using online-based learning video media.. The research method used is descriptive qualitative. The subjects in this study were fifth grade students of SD Atta'Zhimiyah Bandung City with a total of 25 students. The instruments used were teacher and student observation sheets, test questions, and teacher and student interview questionnaires. The results showed that there was an increase in the quality of learning when the learning video media was applied. This is indicated by the average value of IPS understanding in the class of 89.20 which is classified in the good category, the highest score of students is 100 and the lowest value is 60. Student learning mastery shows 92.0% of students getting scores above the minimum completeness criteria and 8, 0% still gets a score below the minimum completeness criteria value.